Rapid profiling of drug-resistant bacteria using DNA-binding dyes and a nanopore-based DNA sequencer - Ayumu Ohno; Kazuo Umezawa; Satomi Asai; Kirill Kryukov; So Nakagawa; Hayato Miyachi; Tadashi Imanishi (Scientific Reports, 2021)
Abstract Spread of drug-resistant bacteria is a serious problem worldwide. We thus designed a new sequence-based protocol that can quickly identify bacterial compositions of clinical samples and their drug-resistance profiles simultaneously. Here we utilized propidium monoazide (PMA) that prohibits DNA amplifications from dead bacteria, and subjected the original and antibiotics-treated samples to 16S rRNA metagenome sequencing. We tested our protocol on bacterial mixtures, and observed that sequencing reads derived from drug-resistant bacteria were significantly increased compared with those from drug-sensitive bacteria when samples were treated by antibiotics. Our protocol is scalable and will be useful for quickly profiling drug-resistant bacteria.